La aplicación de las técnicas grafo-plásticas para potenciar el desarrollo motor fino en las niñas y niños de cuatro a cinco años de edad de la escuela de educación básica 24 de Mayo de la ciudad de Loja, período 2014-2015 - Cabrera Sánchez, Sandra Juliana (2016)
The current research is framed in a descriptive and correlational study about: GRAFO-PLASTIC TECHNIQUES APLICATION TO ENPOWER THE DEVELOPMENT OF A THIN MOTOR IN GIRLS AND BOYS OF 4 AND 5 YEARS AT 24 DE MAYO BASIC EDUCATION SCHOOL, the following objective was set: To determine the importance of grafo-plastic techniques to enpower the development of a thin motor in girls and boys of 4 and 5 years at 24 de Mayo Basic Education School in Loja city, academic year 2014-2015. In the methodological side the following methods were used. The survey, applied to two teachers from initial level I and II. The Dexterímetro de Goddard test, applied to 20 girls and boys to diagnose the development of the fine motor; the intervention with the five grafo-plastic techniques: Ripped, crinkled, punching, modeling and finger-paints worked in class to verify the progress of the development; of the fine motor with the re-application of the Dexterímetro de Goddard test. To sum up: With the application of the diagnostic test Dexterímetro de Goddard it was determined that the majority of children showed a very good 15 % and good level 55% and the others showed a regular 15 % and deficient level 15 % in the development of fine motor. In relation to the re-application of the Dexterímetro de Goddard after the usage of the grafo- techniques: Ripped, crinkled, punching, modeling and finger-paints with girls and boys of initial level, got better in the development of fine motor, getting a level between good 60%, very good 30% and superior 10%, being the strategy a foundamental resource in the reading-writing learning process.